Money (La Crosse, Wisconsin Platinum Disc Corp., 2003)
Twenty-one-year-old Frank Cimballi embarks in a mission to find the men that embezzled his inheritance. He hires a private investigator to track down his father's former business associates and uncover their devious plot to rob him of millions. Frank's search takes him from Kenya to St.Tropez and across the Atlantic to Canada, where he finds Will Scarlet, the financial genius behind his father's business. Will is gravely ill and admits his role in stealing the inheritance. To atone, he agress to help Frank get the last man on his revenge list.
Screenplay by, Gordon Roback and Larry Pederson ; Executive producer, Claudio Mancini ; Associate producer, Ritza Brown ; Original music Enno Morricone.
Bruno Cremer, Maryann D'abo, Anna Kanakis, Bernard Fresson.
Dolby digital.
In English.
Keywords: Feature films